Democratic Control of Military Forces - Smail Ostrakovic (Human Research in Rehabilitation, 2011)
The transition requirement for post communism countries, especially the part that is about military forces is to establish those civil-military relation that will have prepared projects for awareness evolving of society and military about necessity of democratic control over military sector of country through development of many different communication forms and shapes. Before everything, it means the entire freedom and independence of media at access to military forces as the topic and subject of its interests and also the organization of public military communication system as integral part of information-communication system in society.